Ciencia e investigación agraria 2018
DOI: 10.7764/rcia.v45i3.1762
|View full text |Cite
|
Sign up to set email alerts
|

Lupin and pea extrusion decreases the ruminal degradability and improves the true ileal digestibility of crude protein

Abstract: C. Barchiesi, P. Williams, and A. Velásquez. 2018. Extrusion of lupin and pea decrease the ruminal degradability improving true ileal digestibility of crude protein. Cienc. Inv. Agr. 45(3): 231-239. The aim of this work was to evaluate the effect of the extrusion of dehulled lupins (Lupinus albus L.) and peas (Pisum sativum L.) on the ruminal degradability and intestinal digestibility of their protein contents. Ruminal degradability was evaluated in situ in the rumens of two fistulated cows. The true ileal cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Barchiesi-Ferrari and Anrique (2011) found an increase in the CP potential degradable fraction of lupins because of extrusion, but this increase was not biologically significant. Solanas et al (2008) and Barchiesi et al (2018) did not find significant differences, possibly because they used dehulled lupins. Lampart-Szczapa et al (2006) showed lower increases when they used dehulled lupins as they had lower moisture absorbance capacity, which probably affected the Maillard reaction negatively.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Barchiesi-Ferrari and Anrique (2011) found an increase in the CP potential degradable fraction of lupins because of extrusion, but this increase was not biologically significant. Solanas et al (2008) and Barchiesi et al (2018) did not find significant differences, possibly because they used dehulled lupins. Lampart-Szczapa et al (2006) showed lower increases when they used dehulled lupins as they had lower moisture absorbance capacity, which probably affected the Maillard reaction negatively.…”
Section: Resultsmentioning
confidence: 88%
“…Crude protein effective degradability in the current study was similar to the findings of Cros et al (1992) and Aufrère et al (2001), which resulted in an RUP increase of 8.96%, allowing increasing metabolizable protein availability and consequently amino acid availability in the small intestine. Studies by Barchiesi et al (2018) found decreased crude protein effective degradability at an outflow rate of 0.06/h of lupins through extrusion from 82.3% to 72.7%, with an increased true ileal CP digestibility. It is well established that effective protein degradability is negatively related to nitrogen digestibility (Zagorakis et al, 2015).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Total-tract NDF digestibility (TTNDFD), calculated as ruminal NDF digestion + hindgut NDF digestion, has recently been demonstrated to be a good predictor of forage digestibility [ 26 , 27 ]. A large number of studies have been conducted to investigate the ruminal degradability, iNDF, and total-tract digestibility (TTD) of concentrate feeds [ 20 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] and high-quality forages such as CSil [ 26 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], AH [ 41 , 42 , 46 , 48 , 49 , 50 ], and oat hay [ 46 , 48 ] during the last two decades. However, studies on ruminal degradability, iNDF content, intestinal digestibility (ID), and TTD of the crop straws, especially CS, RS, and WS are limited.…”
Section: Introductionmentioning
confidence: 99%